Analysis of Homeschooling Curriculum Policy in Indonesia: CIPPO Approach and International Review - Qalbi, Andi Nur; Ardiyansyah, Muhammad; Munandar, Aris (Riwayat: Educational Journal of History and Humanities, 2025)
Homeschooling in Indonesia is legally recognized as a form of non-formal education under Ministry of Education and Culture Regulation No. 129 of 2014. However, it lacks a standardized national curriculum and evaluation system. This study employs the CIPPO evaluation model (Context, Input, Process, Product, Outcome) to analyze the homeschooling curriculum policy in Indonesia and compare it with practices in the United States, Finland, and Australia. The findings reveal that Indonesias policy remains general and heavily reliant on the capacity of parents and community-based initiatives. In contrast, other countries have implemented clearer regulations, structured curricula, and regular assessment systems to ensure quality and accountability. The CIPPO approach proves effective in identifying both the strengths and weaknesses of homeschooling policies and offers a foundation for improving policy direction toward a more equitable and standardized alternative education system.